Intracranial pressure waveform in patients with essential hypertension - da Costa, Matheus Martins; Sousa, Ana Luiza Lima; Correia, Mikaelle Costa; Inuzuka, Sayuri; Costa, Thiago Oliveira; Vitorino, Priscila Valverde O.; de Toledo Piza, Polyana Vulcano; Frigieri, Gustavo; Coca, Antonio; Barroso, Weimar Kunz Sebba (Frontiers in Cardiovascular Medicine, 2023)
Background There is a strong association between hypertension and cerebrovascular diseases, but most of the mechanistic bases to justify this correlation remains misunderstood. Objective To evaluate intracranial pressure waveform in long-term essential hypertensive patients with a non-invasive device, brain4care (b4c). Methods Cross-sectional study in patients with hypertension. Office blood pressure was measured with an automatic oscillometric device. Intracranial pressure evaluation was acquired through a strain sensor that could detect and monitor nanometric skull bone displacements for each cardiac cycle. Under normal physiological conditions, P1 is greater than P2, and the normal P2/P1 ratio is <1. Time to peak (TTP) is the measurement in seconds of the beginning of waveform inscription until P1 and normal values are <0.20 s. The cut-off points ≥1.2 and ≥0.25 s were used to define intracranial hypertension (ICHT). Results 391 consecutive patients were evaluated (75% female, mean age 64.3 ± 12.0 years). Mean value of P2/P1 ratio was 1.18 ± 0.25 and TTP 0.18 ± 0.63 s The obtained P2/P1 ratios were divided in three categories according to results of previous studies of normalcy (<1.0), intracranial compliance disturbance (1.0–1.19) and ICHT (≥1.2). Normal intracranial pressure was observed in 21.7% of patients, intracranial compliance disturbance in 32.7% and intracranial hypertension in 45.6%. Females showed a higher prevalence of ICHT (50.3%). Conclusion The prevalence of 45.6% intra-cranial hypertension in patients with long-term hypertension, particularly in women, and in those over 65 years old, emphasizes the importance of evaluate intracranial pressure behaviour in these patients and raise a question concerning the real ability of cerebral autoregulation and vascular barriers to protect the brain.